Fine particle full tailings based high strength mine filling cementitious material and method of making
Patent Information
- Application Number
- CN202611264821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-20
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lightweight building materials technology, specifically to a fine-grained, full-tailings-based high-strength mine backfill cementitious material and its preparation method. Background Technology
[0002] A large amount of tailings is generated during the mineral processing of mines. Fine-grained tailings have a high proportion of fine particles, which are characterized by large specific surface area, high surface energy, and small interparticle pores. When it is made into a filling slurry, the fine particles will absorb more mixing water, which will increase the viscosity and transport resistance of the slurry. During the hardening process, some water is also prone to remain around the tailings particles, forming an interface region with relatively concentrated pores.
[0003] Fine-grained tailings typically contain minerals with low reactivity at room temperature, such as quartz and feldspar. While these minerals can serve as skeletal particles for the infill, their bonding ability with the cementitious matrix is limited. When the infill is under load, stress tends to concentrate at the interface between the tailings particles and the cementitious matrix, and cracks easily propagate along this area. Therefore, simply increasing the amount of cementitious material can improve strength, but it will correspondingly increase the infill cost and cannot sufficiently improve the stress state of the tailings particle interface.
[0004] Granulated blast furnace slag possesses potential cementitious activity and can serve as the main active component in backfill cementitious materials. However, the dissolution of the slag glass phase and the formation of subsequent cementitious products require a suitable alkaline and sulfate environment. If the activation rate is too slow, the early load-bearing capacity of the backfill is insufficient; if the activation process is excessively concentrated, the cementitious products may mainly deposit on the outer layer of the slag particles, making it difficult for the internal active substances to continue participating in the reaction. Therefore, fine-grained whole tailings backfill materials not only need to improve the reactivity of the cementitious matrix but also need to simultaneously improve the tailings particle interface and ensure that the interface strengthening process is coordinated with the matrix hardening process.
[0005] When nucleation sites for hydration products are pre-set on the tailings surface, a solid structure can be formed relatively quickly in the interfacial region. However, the effective aluminum species in the slag that can participate in the formation of the aluminum-containing hydration phase need to be released as the glassy phase of the slag gradually dissolves. When both are used together, the early solid phase growth induced by crystal nuclei tends to be faster than the supply of effective aluminum species. This means that when the interface begins to harden, the adjacent matrix cannot simultaneously form sufficient filling and support structures, resulting in the two reinforcing effects not being fully superimposed.
[0006] Therefore, the technical problem to be solved by this invention is to construct a fine-grained tailings interface with the ability to nucleate hydration products without relying on high amounts of cement, expensive organic additives, or high-temperature calcination of tailings, to improve the continuity of early and late reactions in the slag cementitious matrix, and to solve the problem of asynchronous early solid phase growth induced by crystal nuclei and the supply of effective aluminum species in slag, thereby improving the interfacial bonding ability, structural density, and compressive strength of the fine-grained tailings filling body, while taking into account the raw material cost and the operability of engineering preparation. Summary of the Invention
[0007] The purpose of this invention is to provide a fine-grained, full-tailings-based, high-strength mine backfill cementitious material and its preparation method, so as to solve the technical problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a fine-grained, tailings-based, high-strength mine backfill cementitious material includes the following steps: (1) Fine-grained tailings and slaked lime are co-ground, and sodium water glass solution is sprayed into the resulting co-ground material in a mixed state. Then, the material is aged, dried and deagglomerated to obtain modified fine-grained tailings A. (2) Partially dehydrate the desulfurized gypsum to obtain a sulfate carrier containing both β-hemihydrate calcium sulfate and dihydrate calcium sulfate; dry co-grind the granulated blast furnace slag powder, the sulfate carrier, slaked lime and anhydrous sodium sulfate to obtain modified slag B; (3) The modified fine-grained tailings A, modified slag B, metakaolin and limestone powder are dry-mixed to obtain the fine-grained tailings-based mine filling cementitious material.
[0009] Preferably, the fine-grained tailings is unsorted tailings, wherein particles with a diameter less than 74 μm account for no less than 70% of the mass. 90 No larger than 90μm; In step (1), the fine-grained tailings are dried at a temperature not exceeding 70°C until the moisture content is not greater than 1%, and the mass content of Ca(OH)2 in the hydrated lime is not less than 90%. The fine-grained tailings and hydrated lime are co-ground to a co-grinding material of D. 50 8–15 μm, D 90 The material size should not exceed 45μm, and the material temperature during co-grinding should not exceed 50℃.
[0010] Preferably, in step (1), based on 100 parts by weight of dry fine-grained tailings, the amount of hydrated lime is 2.0 to 2.2 parts by weight, and the amount of sodium silicate solution is 4.8 to 5.2 parts by weight. The sodium silicate solution has a solid content of 38%–42% and a modulus n(SiO2) / n(Na2O) of 1.9–2.1. The sodium silicate solution is mixed with process water so that the mass fraction of sodium silicate solid in the resulting spray solution is 8% to 12%, and the total amount of water introduced by the sodium silicate solution and process water is 15 to 18 parts by mass. The spray solution is atomized and sprayed into the co-grinding material within 10 to 20 minutes. After spraying, mixing is continued for 10 to 20 minutes. Then, the mixture is aged under a closed condition at 32 to 38°C for 6 to 8 hours, and then dried at 50 to 55°C until the moisture content is no more than 1%.
[0011] Preferably, in step (2), the desulfurized gypsum is pre-dried at 60-70°C until the free water content is no more than 1%, and then ventilated at 135-145°C for 45-70 minutes. After the treatment, it is cooled to below 50°C. The total mass of the calcium sulfate crystal phase in the sulfate carrier is 100%, the content of the β-hemihydrate calcium sulfate is 60% to 70%, the content of the dihydrate calcium sulfate is 30% to 40%, the content of anhydrous calcium sulfate is not higher than 5%, and the sum of the mass percentages of the three is 100%.
[0012] Preferably, in step (2), based on 100 parts by weight of dry granulated blast furnace slag powder, the amount of sulfate carrier is 7 to 9 parts by weight, the amount of hydrated lime is 3.6 to 4.2 parts by weight, and the amount of anhydrous sodium sulfate is 1.0 to 1.2 parts by weight. The feed moisture content of the dry co-milling process is no more than 0.5%, the relative humidity of the co-milling environment is no more than 40%, and the outlet material temperature is no higher than 50℃. The resulting modified slag B has a specific surface area of 480–520 m². 2 / kg, D 90 No larger than 40μm.
[0013] Preferably, by mass, the modified fine-grained tailings A is 33-37 parts, the modified slag B is 54-58 parts, the metakaolin is 5-6 parts, and the limestone powder is 3-4 parts, and the sum of the mass parts of the above components is 100 parts.
[0014] Preferably, the D of the metakaolinite 50 The limestone powder has a particle size of 3-8 μm and an Al2O3 content of not less than 38% by mass. 50 The material has a particle size of 5–10 μm and a CaCO3 content of not less than 90%, and the mass ratio of metakaolin to limestone powder is 1.5–2.0:1.
[0015] Preferably, the dry mixing in step (3) is carried out under the conditions that the relative humidity of the environment is not greater than 40% and the material temperature is not higher than 45℃, and the dry mixing time is 6 to 8 minutes.
[0016] A fine-grained, tailings-based, high-strength mine backfill cementitious material is prepared by the method described above.
[0017] A mine backfill slurry is composed of the fine-grained tailings-based mine backfill cementitious material, fine-grained tailings that have not been sorted and modified in step (1), and water.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. Enhancement effect of tailings interface nucleation treatment: The reaction degree of minerals such as quartz and feldspar in fine-grained tailings is limited at room temperature. This method does not rely on these minerals participating extensively in the hydration reaction. Instead, it alters the bonding state between the tailings and the cementitious matrix by dispersing and loading hydrated calcium silicate gel on the surface of tailings particles and in the particle contact areas. This gel layer increases the roughness, hydrophilicity, and nucleation sites of hydration products on the tailings surface, allowing subsequent cementitious products to grow continuously along the tailings surface and reducing the loose interface formed by the aggregation of mixing water at particle boundaries. When the hardened body is subjected to pressure, the load can be transferred more evenly from the cementitious matrix to the tailings skeleton, and cracks are less likely to propagate rapidly along the originally smooth, porous particle interfaces, thus improving the interfacial bonding capacity and compressive strength of the filling body.
[0019] 2. Enhancement effect of phase-controlled sulfur release and mechanical activation treatment in slag: After co-grinding, the particle size of slag decreases and the particle size distribution becomes more continuous. Simultaneously, more defects and new reaction interfaces are generated on the glass phase surface, which helps reduce the reaction resistance of subsequent slag hydration. Different calcium sulfate crystal phases in the phase-controlled sulfate carrier have different dissolution and supply rates. Combined with the rapidly soluble sodium sulfate phase, a relatively continuous sulfate supply can be maintained in the early, middle, and late stages of hardening. The resulting early needle-like solid phase can establish an initial support structure between particles, while the subsequently formed gel gradually fills the small pores between the needle bundles and around the slag particles. The two types of solid phases interpenetrate spatially, gradually transforming the matrix from an early skeletal support to a continuous and dense load-bearing structure. This improves early strength while preserving space for continued hydration and pore filling, preventing excessive concentration of strength growth in a single stage.
[0020] 3. Synergistic Effect of Metakaolin and Limestone Powder: After a nucleation layer is formed on the tailings surface, the solid phase formation rate in the interfacial region is significantly accelerated. However, the effective aluminum species in the slag need to be released gradually as the slag glass phase dissolves. When both are used together, a technical problem arises: "the early solid phase growth induced by crystal nuclei is not synchronized with the supply of effective aluminum species." As a result, the tailings interface begins to harden, but the material for forming a stable aluminum-containing solid phase in the adjacent matrix is not yet fully supplied. Some hydration products tend to concentrate on the surface of a few particles, and the fine capillaries between the interface and the matrix cannot be filled synchronously, thus limiting the superposition of the two modification effects. Metakaolin has a higher proportion of amorphous aluminum-silicon structure, and in an alkaline hydration environment, it can provide usable aluminum-silicon sites earlier than slag, compensating for the slower release of effective aluminum species in time. This allows aluminum-containing gels and other stable hydrated solid phases to form synchronously in the adjacent region when the interface begins to form a solid phase structure. Limestone powder acts as a fine-particle filler and disperser, dispersing the growth sites of hydration products from the outer layer of slag particles to the surface of more independent particles, preventing excessive concentration of the solid phase. Simultaneously, the carbonate environment provided by limestone powder is conducive to the stability of the aluminum-containing solid phase, reducing the transformation of the already formed needle-like support structure into a smaller solid phase structure. While metakaolin alone can supplement aluminum-silicon sites, it lacks sufficient dispersion and nucleation surface and stable conditions for the aluminum-containing solid phase. Limestone powder alone, while improving particle size distribution and providing nucleation sites, cannot supplement early-stage available aluminum species. When both are added together, metakaolin primarily addresses the temporal supply of available aluminum species, while limestone powder primarily addresses the spatial distribution and stability of solid phase growth. This allows tailings interface densification, slag matrix hardening, and pore filling to occur continuously within a similar timeframe, thus fully synergistically enhancing the strength gains from both types of modification. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Unless otherwise specified, all quantities below are actual weighed masses, in kg; the quantities of tailings and slag powder are calculated on a dry basis, and the sodium silicate is calculated based on the mass of the commercial solution. All three examples use hydrated lime with a Ca(OH)2 content of 90%, desulfurized gypsum with a CaSO4·2H2O content of not less than 90%, anhydrous sodium sulfate with a purity of not less than 98%, and S95 grade granulated blast furnace slag powder. The total process water volume includes the water contained in the sodium silicate solution; when preparing the filling slurry, if the original tailings contain water, the measured moisture content should be deducted from the added water volume.
[0023] Example 1 A method for preparing a fine-grained, tailings-based, high-strength mine backfill cementitious material includes the following steps: Fine-grained tailings sand that has not undergone particle size separation was selected, of which particles smaller than 74μm accounted for 70%, D 90 The thickness is 90 μm. 100 kg of dry-basis tailings was dried at 60℃ to a moisture content of 1.0%, then 2.0 kg of slaked lime was added, and the mixture was ground together to a density of D. 50 8μm, D 90 The thickness is 40μm, and the material temperature during co-grinding should not exceed 45℃.
[0024] Take 4.8 kg of sodium silicate solution with a solid content of 38% and a modulus n(SiO2) / n(Na2O) of 1.9, which contains 1.824 kg of sodium silicate solid and 2.976 kg of water; add another 15.024 kg of water to make the total process water volume 18.000 kg, and the mass fraction of sodium silicate solid in the resulting spray solution is 9.20%. Under high shear mixing conditions of the co-grinding material, the spray solution is atomized and sprayed in within 10 min, and mixing continues for 10 min. It is then aged in a sealed environment at 32℃ for 6 h, and then dried at 50℃ to a moisture content of 1.0%. After deagglomeration, modified fine-grained tailings A is obtained.
[0025] Take 12.0 kg of desulfurized gypsum, pre-dry it at 60℃ until the free water content is 1.0%, and then ventilate it at 135℃ for 45 min. Stop heating when the mass percentages of β-hemihydrate calcium sulfate, dihydrate calcium sulfate, and anhydrous calcium sulfate in the calcium sulfate crystal phase reach 60%, 40%, and 0%, respectively. Cool to 48℃ and homogenize, then weigh 7.0 kg of this mixture as the sulfate carrier. Mix 100 kg of granulated blast furnace slag powder, 7.0 kg of the sulfate carrier, 3.6 kg of slaked lime, and 1.0 kg of anhydrous sodium sulfate. Dry co-mill under conditions of 0.5% feed moisture content and 40% relative humidity, controlling the outlet material temperature not to exceed 50℃, until the specific surface area reaches 480 m². 2 / kg, D 90 The thickness was 40 μm, resulting in modified slag B.
[0026] Weigh out 37 kg of modified fine-grained tailings A, 54 kg of modified slag B, 6 kg of metakaolin, and 3 kg of limestone powder. The metakaolin's D... 50 The particle size is 3μm, and the Al2O3 content is 38%; the D of the limestone powder 50 The particle size is 5μm and the CaCO3 content is 90%. Under the conditions of 40% relative humidity and material temperature not exceeding 45℃, dry mixing for 6 minutes yields 100kg of cementitious material, with a mass ratio of metakaolin to limestone powder of 2:1.
[0027] Take 100 kg of unmodified fine-grained tailings from the same source and 20 kg of the above-mentioned cementitious material, add 51.43 kg of water to make the solid mass fraction of the slurry 70%. First mix the water and tailings for 1 min, then add the cementitious material and stir for 3 min to obtain the mine filling slurry.
[0028] Example 2 A method for preparing a fine-grained, tailings-based, high-strength mine backfill cementitious material includes the following steps: Fine-grained tailings sand that has not undergone particle size separation was selected, of which particles smaller than 74μm accounted for 78%, D 90 The thickness is 80 μm. 100 kg of dry-basis tailings was dried at 65℃ to a moisture content of 0.8%, then 2.1 kg of slaked lime was added, and the mixture was ground together to a density of D. 50 12μm, D 90 The thickness is 42μm, and the material temperature during co-grinding should not exceed 48℃.
[0029] Take 5.0 kg of sodium silicate solution with a solid content of 40% and a modulus n(SiO2) / n(Na2O) of 2.0, which contains 2.0 kg of sodium silicate solid and 3.0 kg of water; add another 12.0 kg of water to make the total process water volume 15.0 kg. The mass fraction of sodium silicate solid in the resulting spray solution is 11.76%. Under high shear mixing conditions, the spray solution is atomized and sprayed into the co-grinding material within 15 min, and mixing continues for another 15 min. After aging in a sealed environment at 35℃ for 7 h, it is dried at 52℃ to a moisture content of 0.8%. After deagglomeration, modified fine-grained tailings A is obtained.
[0030] Take 12.0 kg of desulfurized gypsum, pre-dry it at 65℃ until the free water content is 0.8%, and then ventilate it at 140℃ for 58 min. Stop heating when the mass percentages of β-hemihydrate calcium sulfate, dihydrate calcium sulfate, and anhydrous calcium sulfate in the calcium sulfate crystal phase reach 65%, 33%, and 2%, respectively. Cool to 45℃ and homogenize, then weigh 8.0 kg of this mixture as the sulfate carrier. Mix 100 kg of granulated blast furnace slag powder, 8.0 kg of the sulfate carrier, 3.9 kg of slaked lime, and 1.1 kg of anhydrous sodium sulfate. Dry co-mill the mixture under conditions of 0.3% feed moisture content and 35% relative humidity, controlling the outlet material temperature to not exceed 48℃, until the specific surface area reaches 500 m². 2 / kg, D 90 The thickness was 38 μm, resulting in modified slag B.
[0031] Weigh out 33 kg of modified fine-grained tailings A, 57 kg of modified slag B, 6 kg of metakaolin, and 4 kg of limestone powder. The metakaolin's D... 50 The particle size is 5.5 μm, and the Al2O3 content is 42%; the D of the limestone powder 50The particle size is 7.5 μm and the CaCO3 content is 95%. Under the conditions of relative humidity of 35% and material temperature not exceeding 40℃, dry mixing for 7 minutes yields 100 kg of cementitious material, with a mass ratio of metakaolin to limestone powder of 1.5:1.
[0032] Take 100 kg of unmodified fine-grained tailings from the same source and 22.5 kg of the above-mentioned cementitious material, add 47.64 kg of water to make the solid mass fraction of the slurry 72%. First mix the water and tailings for 1.5 min, then add the cementitious material and stir for 4 min to obtain the mine filling slurry.
[0033] Example 3 A method for preparing a fine-grained, tailings-based, high-strength mine backfill cementitious material includes the following steps: Fine-grained tailings sand that has not undergone particle size separation was selected, of which particles smaller than 74μm accounted for 85%, D 90 The thickness is 70 μm. 100 kg of dry-basis tailings was dried at 70℃ to a moisture content of 0.5%, then 2.2 kg of slaked lime was added, and the mixture was ground together to a density of D. 50 15μm, D 90 The thickness is 45μm, and the material temperature during co-grinding should not exceed 50℃.
[0034] Take 5.2 kg of sodium silicate solution with a solid content of 42% and a modulus n(SiO2) / n(Na2O) of 2.1, which contains 2.184 kg of sodium silicate solid and 3.016 kg of water; add another 13.000 kg of water to make the total process water volume 16.016 kg, and the mass fraction of sodium silicate solid in the resulting spray solution is 12.00%. Under high shear mixing conditions of the co-grinding material, the spray solution is atomized and sprayed in within 20 min, and mixing continues for another 20 min. It is then aged in a sealed environment at 38℃ for 8 h, and then dried at 55℃ to a moisture content of 0.5%. After deagglomeration, modified fine-grained tailings A is obtained.
[0035] Take 12.0 kg of desulfurized gypsum, pre-dry it at 70℃ until the free water content is 0.5%, and then ventilate it at 145℃ for 70 min. Stop heating when the mass percentages of β-hemihydrate calcium sulfate, dihydrate calcium sulfate, and anhydrous calcium sulfate in the calcium sulfate crystal phase reach 70%, 30%, and 0%, respectively. Cool to 40℃ and homogenize, then weigh 9.0 kg of this mixture as the sulfate carrier. Mix 100 kg of granulated blast furnace slag powder, 9.0 kg of the sulfate carrier, 4.2 kg of slaked lime, and 1.2 kg of anhydrous sodium sulfate. Dry co-mill under conditions of 0.2% feed moisture content and 30% relative humidity, controlling the outlet material temperature not to exceed 45℃, until the specific surface area reaches 520 m². 2 / kg, D 90 The thickness was 35 μm, resulting in modified slag B.
[0036] Weigh out 34 kg of modified fine-grained tailings A, 58 kg of modified slag B, 5 kg of metakaolin, and 3 kg of limestone powder. The metakaolin's D... 50 The limestone powder has a particle size of 8 μm and an Al2O3 content of 45%; the D... 50 The particle size is 10μm and the CaCO3 content is 98%. Under the conditions of relative humidity of 30% and material temperature not exceeding 35℃, dry mixing for 8 minutes yields 100kg of cementitious material, with a mass ratio of metakaolin to limestone powder of 1.67:1.
[0037] Take 100 kg of unmodified fine-grained tailings from the same source and 25 kg of the above-mentioned cementitious material, add 43.92 kg of water to make the solid mass fraction of the slurry 74%. First mix the water and tailings for 2 minutes, then add the cementitious material and stir for 5 minutes to obtain the mine filling slurry.
[0038] Comparative Example 1: The 37 kg of modified fine-grained tailings A in Example 1 was replaced with 37 kg of unmodified fine-grained tailings powder from the same source. The D of the unmodified fine-grained tailings powder 50 and D 90 The thicknesses were 8μm and 40μm, respectively, and the remaining raw materials, dosages, and process conditions were the same as in Example 1.
[0039] Comparative Example 2: The same raw materials and amounts as in Example 1 were used, but the quicklime was first mixed with the diluted sodium silicate spray solution for 10 minutes, and then the resulting mixture was added to the fine-grained tailings. All other preparation conditions were the same as in Example 1.
[0040] Comparative Example 3: The 54 kg of modified slag B in Example 1 was replaced with 54 kg of slag with a specific surface area of 480 m². 2 / kg and D 90 The raw materials, dosages, and process conditions were the same as in Example 1, and the unmodified S95 grade granulated blast furnace slag powder with a diameter of 40 μm was used.
[0041] Comparative Example 4: When preparing modified slag B, the 7.0 kg phase-controlled sulfate carrier in Example 1 was replaced with 7.0 kg of dried dihydrate desulfurized gypsum that had not undergone partial dehydration treatment. The other raw materials, dosages and process conditions were the same as in Example 1.
[0042] Comparative Example 5: When preparing modified slag B, 1.0 kg of anhydrous sodium sulfate was not added, and 1.0 kg of granulated blast furnace slag powder was added accordingly to keep the total mass of the powder unchanged. The other raw materials, dosages and process conditions were the same as in Example 1.
[0043] Comparative Example 6: The 6 kg metakaolin and 3 kg limestone powder of Example 1 were not added. Instead, they were replaced with high-purity quartz powder of equal mass and similar particle size. Other raw materials, dosages and process conditions were the same as in Example 1.
[0044] Comparative Example 7: The 6 kg metakaolin from Example 1 was retained, and 3 kg of limestone powder was replaced with 3 kg of high-purity quartz powder with a D50 of 5 μm. The remaining raw materials, dosages and process conditions were the same as in Example 1.
[0045] Comparative Example 8: The 3 kg limestone powder from Example 1 was retained, and the 6 kg metakaolin was replaced with 6 kg of high-purity quartz powder with a D50 of 3 μm. The remaining raw materials, dosages and process conditions were the same as in Example 1.
[0046] Performance testing 1. Sample Preparation. All raw materials were prepared according to the feeding amounts, order of addition, and mixing conditions specified in the corresponding examples or comparative proportions. The amounts of tailings and other water-containing raw materials were calculated on a dry basis, and the mixing water was deducted based on their actual moisture content to ensure that the actual solid mass concentration of the slurry was consistent with the corresponding scheme. The raw materials, mixing water, and molds used in the experiment were placed in an environment of 20±2℃ for no less than 24 hours beforehand. Spread, bleeding rate, and setting time were tested using three independently prepared batches of slurry. The results in Table 1 are the arithmetic mean of the three batches of tests. For unconfined compressive strength, three parallel specimens were prepared for each formulation and each age.
[0047] 2. Spread Test. Since the filling slurry of this invention uses fine-grained tailings sand and does not contain waste rock, crushed stone, or other coarse aggregates, the spread is measured according to Article 3.7.4 and Appendix B of GB / T 51450—2022 "Technical Standard for Filling Engineering in Metal and Non-metal Mines," instead of the slump method for coarse aggregate slurries. Three minutes after mixing, the spread cylinder and horizontal base plate specified in Appendix B are moistened and any standing water is removed. The slurry is continuously filled into the spread cylinder, the top is leveled, and no vibration is performed. Then, the spread cylinder is lifted vertically and smoothly. After the slurry stops flowing, two spread diameters perpendicular to each other are measured. The arithmetic mean of the two diameters is taken as the spread, accurate to 1 mm.
[0048] 3. Bleeding Rate Test. The bleeding rate was determined according to GB / T 50080—2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" referenced in Clause 3.7.2 of GB / T 51450—2022. Freshly mixed slurry was placed into a covered container as specified in the standard, and the mass of the container and the total mass of the container and slurry were recorded. The surface was leveled and allowed to stand. For the first 60 minutes, surface bleeding water was sampled every 10 minutes, and thereafter every 30 minutes, until no further bleeding water was observed after three consecutive observations. The collected bleeding water was weighed and calculated according to B=m b / m w,s Calculate the bleeding rate by multiplying by 100%, where m b To calculate the cumulative quality of the effluent, m w,s The initial water content of the sample is calculated based on the mix proportion and the sample mass in the container, with the result accurate to 0.1%.
[0049] 4. Setting Time Test. The initial setting time and final setting time are determined according to the penetration resistance method in GB / T 50080-2016, as referenced in Clause 3.7.2 of GB / T 51450—2022. The starting point for timing is the moment when the mixing water first contacts the cementitious material. Since the particle size of the tailings sand in this invention is less than 5mm, the uniform slurry can be directly loaded into the penetration resistance test container and left to stand in an environment of 20±2℃ and relative humidity not less than 90%. During the test, a penetration probe of suitable area is selected and vertically penetrated to a specified depth within a specified time. The penetration force F is recorded, and the result is calculated according to R... p The penetration resistance is calculated as F / A, where A is the cross-sectional area of the probe. The times when the penetration resistance reaches 3.5 MPa and 28.0 MPa are determined by interpolation based on the penetration resistance-time curve, and these are used as the initial setting time and final setting time, accurate to 1 minute. This system is a tailings-containing filler slurry; therefore, the Vicat apparatus initial and final setting methods, which are only applicable to cement standard consistency neat slurry, are not used.
[0050] 5. Unconfined compressive strength test. The unconfined compressive strength was determined according to Section 3.8 of GB / T 51450—2022. The slurry was slowly poured into a cylindrical mold with an inner diameter of 75 mm and a height of 150 mm. Large air bubbles were gently tapped to remove them, the mold was leveled, and a sealing film was applied. The specimen was cured in the mold at 20±2℃ and relative humidity greater than 90% for 24±2 hours without damage, and then demolded. Curing continued for 3 days, 7 days, and 28 days. Before testing, both ends of the specimen were ground smooth, the height was measured, and the diameter was measured six times along two mutually perpendicular directions at the top, middle, and bottom. The average value was used as the calculated diameter. The specimen axis was aligned with the center of the pressure plate of the compression testing machine. A continuous and uniform load was applied, ensuring that the time from the start of loading to failure was not less than 2 minutes. The failure load F was recorded, and calculated according to f=4F / πd. 2 Calculate the strength. Take the arithmetic mean of the three specimens, accurate to 0.01 MPa; if the difference between an extreme value and the median value exceeds 15% of the median value, take the median value; if both extreme values exceed the limit, the test group should be repeated.
[0051] Table 1:
[0052] Compared to Example 1, Comparative Example 1, after using unmodified fine tailings, showed a decrease in strength at 3d, 7d, and 28d by 17.9%, 16.3%, and 16.3%, respectively, while the bleeding rate increased from 1.8% to 3.0%. This indicates that tailings surface conditioning helps reduce free water accumulation at particle interfaces and improves the interfacial bearing capacity of the hardened body. In Comparative Example 2, after changing the order of adding hydrated lime and water glass, the spread decreased to 221 mm, but the bleeding rate increased to 3.5%, and the 28-day strength was only 5.01 MPa. This suggests that premature local flocculation, while making the slurry appear thicker, fails to form a uniform and continuous reinforcing interface, thus the loss of fluidity does not translate into corresponding strength gains.
[0053] In Comparative Example 3, after replacing the modified slag with S95 slag of the same fineness without phase-controlled sulfur release treatment, the initial and final setting times were extended to 426 min and 671 min, respectively, and the strengths at 3d, 7d, and 28d were only 1.09 MPa, 2.33 MPa, and 4.31 MPa, respectively. Compared to Comparative Example 1, the strengths at the three ages increased by 100.0%, 66.1%, and 46.6%, respectively, indicating that the phase-controlled sulfur release-mechanical activation treatment of slag has the most significant impact on early structure formation and can continue into later stages. In Comparative Example 4, after eliminating the calcium sulfate phase composition control, and in Comparative Example 5, after eliminating sodium sulfate, the 3d strengths decreased to 1.68 MPa and 1.51 MPa, respectively, while the 28d strengths still reached 5.46 MPa and 5.61 MPa, reflecting that the lack of relevant components has a greater impact on early performance than later performance, and continued hardening in later stages can only partially compensate for insufficient early structure formation.
[0054] The combination of metakaolin and limestone powder mainly addresses the contradiction that "metakaolin, when used alone, has a high water requirement and excessive thickening effect, while limestone powder, when used alone, mainly acts as a filler with limited later-stage strength." In Comparative Example 6, without either material, the 3-day, 7-day, and 28-day strengths were 1.42 MPa, 2.70 MPa, and 4.55 MPa, respectively. In Comparative Example 7, with metakaolin alone, these strengths increased to 1.82 MPa, 3.26 MPa, and 5.35 MPa, respectively; and in Comparative Example 8, with limestone powder alone, these strengths increased to 1.59 MPa, 2.97 MPa, and 4.92 MPa, respectively. Using Comparative Example 6 as a common benchmark, if the two materials only produce a simple additive effect, the 3-day, 7-day, and 28-day strengths of the complete system should be 1.99 MPa, 3.53 MPa, and 5.72 MPa, respectively. However, the corresponding values for Example 1 are 2.18 MPa, 3.87 MPa, and 6.32 MPa, which are 0.19 MPa, 0.34 MPa, and 0.60 MPa higher, respectively, indicating a positive interaction. Simultaneously, Example 1 has a spread 5 mm higher than Comparative Example 7, which only contains metakaolin, but a 0.7 percentage point lower bleeding rate. This indicates that limestone powder, by optimizing the fine particle size distribution and dispersion state, can mitigate the loss of fluidity caused by metakaolin; while metakaolin compensates for the insufficient bonding reinforcement when limestone powder is used alone. With both working together, fine particle filling, moisture retention, and the continuity of the hardened skeleton are balanced, thus improving strength at all ages while maintaining transportability.
[0055] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a fine-grained, tailings-based, high-strength mine backfill cementitious material, characterized in that, Includes the following steps: (1) Fine-grained tailings and slaked lime are co-ground, and sodium water glass solution is sprayed into the resulting co-ground material in a mixed state. Then, the material is aged, dried and deagglomerated to obtain modified fine-grained tailings A. (2) Partially dehydrate the desulfurized gypsum to obtain a sulfate carrier containing both β-hemihydrate calcium sulfate and dihydrate calcium sulfate; dry co-grind the granulated blast furnace slag powder, the sulfate carrier, slaked lime and anhydrous sodium sulfate to obtain modified slag B; The total mass of the calcium sulfate crystal phase in the sulfate carrier is 100%, the content of the β-hemihydrate calcium sulfate is 60% to 70%, the content of the dihydrate calcium sulfate is 30% to 40%, the content of anhydrous calcium sulfate is not higher than 5%, and the sum of the mass percentages of the three is 100%; Based on 100 parts by weight of dry granulated blast furnace slag powder, the amount of sulfate carrier is 7-9 parts by weight, the amount of hydrated lime is 3.6-4.2 parts by weight, and the amount of anhydrous sodium sulfate is 1.0-1.2 parts by weight. (3) The modified fine-grained tailings A, modified slag B, metakaolin and limestone powder are dry-mixed to obtain the fine-grained tailings-based mine filling cementitious material.
2. The preparation method according to claim 1, characterized in that, The fine-grained tailings are unsorted tailings, wherein the mass percentage of particles with a diameter less than 74 μm is not less than 70%, and the D90 is not greater than 90 μm. In step (1), the fine-grained tailings are dried at a temperature not exceeding 70°C until the moisture content is not greater than 1%, and the mass content of Ca(OH)2 in the hydrated lime is not less than 90%. The fine-grained tailings and hydrated lime are co-ground until the D50 of the co-ground material is 8-15 μm and the D90 is no greater than 45 μm, and the material temperature during the co-grinding process is no higher than 50℃.
3. The preparation method according to claim 2, characterized in that, In step (1), based on 100 parts by weight of dry fine-grained tailings, the amount of slaked lime used is 2.0 to 2.2 parts by weight, and the amount of sodium silicate solution used is 4.8 to 5.2 parts by weight. The sodium silicate solution has a solid content of 38%–42% and a modulus n(SiO2) / n(Na2O) of 1.9–2.
1. The sodium silicate solution is mixed with process water so that the mass fraction of sodium silicate solid in the resulting spray solution is 8% to 12%, and the total amount of water introduced by the sodium silicate solution and process water is 15 to 18 parts by mass. The spray solution is atomized and sprayed into the co-grinding material within 10 to 20 minutes. After spraying, mixing is continued for 10 to 20 minutes. Then, the mixture is aged under a closed condition at 32 to 38°C for 6 to 8 hours, and then dried at 50 to 55°C until the moisture content is no more than 1%.
4. The preparation method according to claim 1, characterized in that, In step (2), the desulfurized gypsum is pre-dried at 60-70°C until the free water content is no more than 1%, and then ventilated at 135-145°C for 45-70 minutes. After the treatment, it is cooled to below 50°C.
5. The preparation method according to claim 4, characterized in that, In step (2), the feed moisture content of the dry co-milling process is no more than 0.5%, the relative humidity of the co-milling environment is no more than 40%, the outlet material temperature is no higher than 50℃, and the specific surface area of the resulting modified slag B is 480-520 m². 2 / kg, D90 not greater than 40μm.
6. The preparation method according to claim 1, characterized in that, In step (3), by mass, the modified fine-grained tailings A is 33-37 parts, the modified slag B is 54-58 parts, the metakaolin is 5-6 parts, the limestone powder is 3-4 parts, and the sum of the mass parts of the above components is 100 parts.
7. The preparation method according to claim 6, characterized in that, The metakaolin has a D50 of 3-8 μm and an Al2O3 content of not less than 38% by mass, the limestone powder has a D50 of 5-10 μm and a CaCO3 content of not less than 90% by mass, and the mass ratio of the metakaolin to the limestone powder is 1.5-2.0:
1.
8. The preparation method according to claim 6, characterized in that, The dry mixing in step (3) is carried out under the conditions that the relative humidity of the environment is not greater than 40% and the material temperature is not higher than 45℃, and the dry mixing time is 6 to 8 minutes.
9. A fine-grained, tailings-based, high-strength mine backfill cementitious material, characterized in that... It is prepared by the method described in any one of claims 1 to 8.
10. A mine filling slurry, characterized in that, It is composed of the fine-grained tailings-based mine filling cementitious material as described in claim 9, fine-grained tailings that have not been sorted and modified in step (1), and water.
Citation Information
Patent Citations
Preparation process of iron tailing cement-based high-strength curb
CN118344105A
Soil stabilizer based on multi-element solid waste and use method thereof
CN121873812A